The potential regulatory role of mannose phosphotransferase system EII in alkaline resistance of Enterococcus faecalis - Runze Liu; Yi Luo; Pei Liu; Shuo Xiao; Wei Fan; Bing Fan (Journal of Oral Microbiology)
Objective To investigate the role of mannose phosphotransferase system (Man-PTS) EII in the alkaline resistance of Enterococcus faecalis (E. faecalis).Methods The Man-PTS EIID (mptD) deletion (ΔmptD) and overexpressing (+mptD) strains of E. faecalis were constructed. The contribution of the Man-PTS EII to alkaline resistance was investigated by assessing growth and biofilm formation of E. faecalis at pH 7 and 10, as well as changes in intracellular ATP levels, pH, potassium ion concentration, membrane potential and membrane permeability. The effects of mptD on the expression of other Man-PTS EII components and membrane transport-related genes were evaluated by RT-qPCR at pH 10. In addition, six clinical strains were isolated. Three strains of E. faecalis with high to low alkaline resistance were screened, and RNA sequencing was performed to further explore the role of Man-PTS EII in the alkaline resistance.Results mptD enhanced the alkaline resistance of E. faecalis by maintaining pH homeostasis in an alkaline environment. Overexpression of mptD induced membrane hyperpolarization, reduced membrane permeability, decreased intracellular K+ levels, lowered cytoplasmic pH, and elevated ATP production, while the loss of mptD reversed these effects (p < 0.05). mptD coordinated the expression of Man-PTS EII components and upregulated genes encoding membrane transporter components (p < 0.01). All Man-PTS EII components were positively related to the degree of alkaline resistance of E. faecalis (p < 0.05).Conclusion Man-PTS EII is a key factor in the interaction between metabolism and ion membrane transport during the alkaline resistance process of E. faecalis. This study may provide new insights for understanding the alkaline resistance of E. faecalis.